Between a Reef and a Hard Place: Capacity to Map the Next Coral Reef Catastrophe - Hickey, Sharyn M.; Radford, Ben; Roelfsema, Chris M.; Joyce, Karen E.; Wilson, Shaun K.; Marrable, Daniel; Barker, Kathryn; Wyatt, Mathew; Davies, Harriet N.; Leon, Javier X.; Duncan, John; Holmes, Thomas H.; et al. (Frontiers in Marine Science, 2020)
Increasing sea surface temperature and extreme heat events pose the greatest threat to coral reefs globally, with trends exceeding previous norms. The resultant mass bleaching events, such as those evidenced on the Great Barrier Reef in 2016, 2017, and 2020 have substantial ecological costs in addition to economic and social costs. Advancing remote (nanosatellites, rapid revisit traditional satellites) and in-field (drones) technological capabilities, cloud data processing, and analysis, coupled with existing infrastructure and in-field monitoring programs, have the potential to provide cost-effective and timely information to managers allowing them to better understand changes on reefs and apply effective remediation. Within a risk management framework for monitoring coral bleaching, we present an overview of how remote sensing can be used throughout the whole risk management cycle and highlight the role technological advancement has in earth observations of coral reefs for bleaching events.